Coal gangue hollow brick with excellent anti-seismic property
By adding seismic agents and reinforcement in the preparation process of coal gangue hollow bricks, the problem of poor seismic resistance of coal gangue hollow bricks in the prior art is solved, and higher seismic resistance and mechanical properties are achieved, which is suitable for building applications with high seismic resistance requirements.
Patent Information
- Application Number
- CN202411678192.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the seismic resistance of coal gangue hollow bricks is poor, which is difficult to meet the demand for seismic resistance in buildings.
By adding seismic and reinforcement agents, including straw, steel slag powder, bamboo charcoal, silica, polypropylene fiber and other components in the preparation process of coal gangue hollow bricks, the seismic and mechanical properties of hollow bricks are improved.
It significantly improves the seismic and mechanical properties of coal gangue hollow bricks, enhances the compressive strength and durability of the bricks, and is suitable for building applications with high seismic resistance.
Smart Images

Figure BDA0005147583620000111 
Figure BDA0005147583620000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of building material production, and in particular to a hollow coal gangue brick with excellent earthquake resistance. Background Art
[0002] Coal gangue hollow brick is a kind of energy-saving wall material, mainly used in permanent buildings instead of solid clay bricks. Because this product has light weight, high strength, good bearing, earthquake resistance, heat preservation, heat insulation and sound insulation performance. In addition, when used, the construction period is short and the comprehensive cost is low, so it has a broad market. The widespread use of this sintered brick has great practical significance for protecting and saving arable land, managing the environment, alleviating the energy crisis, improving building functions, improving living conditions, and realizing the modernization of the residential industry.
[0003] Gangue is mostly composed of clay rock and limestone clay, which contains residual carbon and a certain amount of calorific value. When it is actually roasted, it basically does not need to be fed with coal, but can be roasted with its own calorific value. Therefore, using gangue as a raw material to burn into building materials products - gangue hollow bricks, basically does not require fuel and can be used in building design and construction.
[0004] Patent technology document CN103420666A discloses a hollow brick of ore tailings ceramsite and a preparation method thereof, which is made of the following raw materials in parts by weight: 20-30 of shale, 30-50 of coal gangue, 15-20 of building waste, 10-15 of modified loess, 8-12 of quicklime powder, 15-25 of ore tailings, 5-10 of rice husk, 8-12 of barite, 10-15 of limestone, 5-10 of volcanic ash, 3-6 of aluminum silicate fiber, 2-4 of calcium sulfate whiskers, and an appropriate amount of water. The hollow brick produced by the ceramsite made from ore tailings as the main raw material of the present invention not only reduces the large amount of arable land occupied by iron ore tailings due to accumulation, reduces environmental pollution, but also improves the thermal insulation performance of hollow bricks. However, the hollow bricks prepared by the prior art by simply mixing various ores have poor seismic performance.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a hollow coal gangue brick with excellent seismic performance. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a hollow coal gangue brick with excellent seismic performance to solve the problem of poor seismic performance of hollow coal gangue bricks in the prior art.
[0007] Based on the above purpose, the present invention provides a hollow coal gangue brick with excellent earthquake resistance.
[0008] A hollow coal gangue brick with excellent earthquake resistance is prepared from the following raw materials in parts by weight: 60-80 parts of coal gangue, 25-30 parts of calcium carbide mud, 50-55 parts of red mud, 20-30 parts of clay, 10-20 parts of white ash slag, 10-15 parts of phosphogypsum, 5-10 parts of earthquake-resistant agent, 3-5 parts of reinforcing agent, and 17-20 parts of water;
[0009] The anti-seismic agent is prepared from straw, steel slag powder, bamboo charcoal, silicon dioxide, polypropylene fiber and water reducing agent;
[0010] The reinforcing agent is prepared from rubber powder, silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose and a water reducing agent.
[0011] Preferably, the preparation method of the anti-vibration agent is as follows:
[0012] Step A1: carbonizing the straw at 500-700° C. for 2-3 hours, adding steel slag powder, bamboo charcoal, silicon dioxide, and polypropylene fiber after cooling, mixing and crushing to obtain a straw mixture;
[0013] Step A2: Add the straw mixture into water, stir for 2-3 hours, add a water reducer, mix, stir at 55-60° C. for 30-35 minutes, pass into a spray drying device and dry for 3-5 hours to obtain an anti-seismic agent.
[0014] Preferably, in step A1, the mass ratio of straw, steel slag powder, bamboo charcoal, silicon dioxide and polypropylene fiber is 8-10:3-5:5-8:3-5:5-8.
[0015] Preferably, in step A2, the mass ratio of the straw mixture, water and water reducing agent is 8-12:3-5:1-3.
[0016] Preferably, the preparation method of the enhancer is as follows:
[0017] Add rubber powder into a mixer, dry mix for 5-8 minutes, then add silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose and water and stir for 3-5 minutes, finally add a water reducer and stir for 20-25 minutes to obtain a reinforcing agent.
[0018] Preferably, the mass ratio of the rubber powder, silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose, water and water reducing agent is 20-30:5-8:3-5:2-5:3-5:8-10:1-3.
[0019] Preferably, the preparation method of the hollow coal gangue brick with excellent seismic performance is as follows:
[0020] Step B1: using a hammer crusher to crush coal gangue, calcium carbide mud, red mud, clay, lime slag and phosphogypsum respectively, and sieving to obtain a mixed raw material;
[0021] Step B2: After the mixed raw materials are treated by an electromagnetic iron remover, water and an anti-vibration agent are added and stirred for 25-30 minutes to obtain a mixed mud;
[0022] Step B3: The mixed mud material is put into the aging warehouse through the assembly line and sealed for aging for 2-3 days, during which time it is sprayed with moisturizing agent;
[0023] Step B4: The aged mixed mud material is homogenized and then fed into a brick making machine to be made into brick blanks;
[0024] Step B5: coating a reinforcing agent on the surface of the bricks, sending the bricks into a drying chamber for gradient drying, and then sending the dried bricks into a tunnel kiln for sintering to obtain hollow coal gangue bricks with excellent earthquake resistance.
[0025] Preferably, the particle size of the mixed raw material in step B1 is 0.2-0.5 mm.
[0026] Preferably, the aging in step B3 is maintained at a temperature of 25-30° C. and a pressure of 400-600 KPa.
[0027] Preferably, the gradient drying in step B5 is drying at 50-60°C for 3-5h, drying at 60-70°C for 5-8h, and drying at 80-100°C for 8-10h;
[0028] The sintering temperature in step B5 is 1000-1050° C., and the sintering time is 6-8 hours.
[0029] Beneficial effects of the present invention:
[0030] The invention provides a hollow coal gangue brick with excellent anti-seismic performance. The hollow brick is prepared with coal gangue as the main raw material, and has the characteristics of reasonable process design, simple operation, energy saving, comprehensive utilization of waste, etc. The anti-seismic performance and mechanical properties of the hollow brick are improved by adding an anti-seismic agent and a reinforcing agent in the preparation process of the hollow brick; the straw ash in the anti-seismic agent can enhance the compressive strength of the hollow brick and help solidify the brick body; the silicon dioxide in the anti-seismic agent and the reinforcing agent can increase the hardness and durability of the brick body, can form a stable silicon-oxygen bond network, and improve the mechanical strength of the hollow brick; the performance of the hollow brick is enhanced by adding the anti-seismic agent in the preparation process of the hollow brick and coating the reinforcing agent on the surface of the brick blank; at the same time, the best performance effect is achieved by adjusting the particle size, aging time and drying time of the raw materials, and the hollow brick has broad application prospects. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0032] The sources and properties of some of the raw materials used in the present invention are as follows:
[0033] Silicon dioxide was purchased from Tianjin Xiensiopude Technology Co., Ltd.; calcium lignin sulfonate was purchased from Tianjin Xiensiopude Technology Co., Ltd.; carboxymethyl cellulose was purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0034] Embodiment 1: A hollow coal gangue brick with excellent earthquake resistance comprises the following steps:
[0035] S1: 8 g of straw was carbonized at 500 °C for 2 h, and after cooling, 3 g of steel slag powder, 5 g of bamboo charcoal, 3 g of silicon dioxide, and 5 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0036] S2: 8g of straw mixture was added to 3g of water, stirred for 2h, 1g of water reducer was added, mixed and stirred at 55°C for 30min, and dried in a spray drying equipment for 3h to obtain an anti-seismic agent;
[0037] S3: Add 20g of rubber powder into a mixer, dry mix for 5min, then add 5g of silicon dioxide, 3g of calcium lignin sulfonate, 2g of sodium metasilicate, 3g of carboxymethyl cellulose and 8g of water and stir for 3min, finally add 1g of water reducer and stir for 20min to obtain a reinforcing agent;
[0038] S4: using a hammer crusher to crush 60g of coal gangue, 25g of calcium carbide mud, 50g of red mud, 20g of clay, 10g of lime slag and 10g of phosphogypsum respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.2mm;
[0039] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 17 g of water and 5 g of an anti-vibration agent are added and stirred for 25 min to obtain a mixed mud;
[0040] S6: The mixed mud enters the aging warehouse through the assembly line and is sealed for aging for 2 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 25°C and the pressure is 400KPa;
[0041] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0042] S8: Coat 3g of reinforcing agent on the surface of the brick, send it into a drying room and dry it at 50℃ for 3h, 60℃ for 5h, and 80℃ for 8h. Then send the dried brick to a tunnel kiln and sinter it at 1000℃ for 6h to obtain hollow coal gangue bricks with excellent seismic performance.
[0043] Embodiment 2: A hollow coal gangue brick with excellent earthquake resistance comprises the following steps:
[0044] S1: 8.5 g of straw was carbonized at 550°C for 2.2 h, and after cooling, 3.5 g of steel slag powder, 6 g of bamboo charcoal, 3.5 g of silicon dioxide, and 6 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0045] S2: 9 g of straw mixture was added to 3.5 g of water, stirred for 2.2 h, and then 1.5 g of water reducer was added. After mixing, the mixture was stirred at 56 °C for 31 min, and then dried in a spray drying equipment for 3.5 h to obtain an anti-seismic agent;
[0046] S3: Add 22g of rubber powder into a mixer, dry mix for 6min, then add 6g of silicon dioxide, 3.5g of calcium lignin sulfonate, 3g of sodium metasilicate, 3.5g of carboxymethyl cellulose and 8.5g of water and stir for 3.5min, finally add 1.5g of water reducer and stir for 22min to obtain a reinforcing agent;
[0047] S4: using a hammer crusher to crush 65g of coal gangue, 26g of calcium carbide mud, 51g of red mud, 22g of clay, 12g of lime slag and 11g of phosphogypsum, respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.3mm;
[0048] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 18 g of water and 6 g of an anti-vibration agent are added and stirred for 26 min to obtain a mixed mud;
[0049] S6: The mixed mud material is passed through the assembly line into the aging warehouse and sealed for aging for 2 days, during which time it is sprayed with moisture, wherein the aging temperature is maintained at 22°C and the pressure is 450KPa;
[0050] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0051] S8: Coat 3.5g of reinforcing agent on the surface of the brick, send it into a drying room and dry it at 52℃ for 3.5h, 62℃ for 6h, and 85℃ for 8.5h. Then send the dried brick to a tunnel kiln and sinter it at 1010℃ for 6.5h to obtain hollow coal gangue bricks with excellent seismic performance.
[0052] Embodiment 3: A hollow coal gangue brick with excellent earthquake resistance comprises the following steps:
[0053] S1: 9 g of straw was carbonized at 600 °C for 2.4 h, and after cooling, 4 g of steel slag powder, 6.5 g of bamboo charcoal, 4 g of silicon dioxide, and 6.5 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0054] S2: 10g of straw mixture was added to 4g of water, stirred for 2.4h, then 2g of water reducer was added, mixed and stirred at 57°C for 32min, and dried in a spray drying equipment for 4h to obtain an anti-seismic agent;
[0055] S3: Add 24 g of rubber powder into a mixer, dry mix for 6.5 min, then add 6.5 g of silicon dioxide, 4 g of calcium lignin sulfonate, 3.5 g of sodium metasilicate, 4 g of carboxymethyl cellulose and 9 g of water and stir for 4 min, finally add 2 g of water reducer and stir for 23 min to obtain a reinforcing agent;
[0056] S4: using a hammer crusher to crush 70g of coal gangue, 27g of calcium carbide mud, 52g of red mud, 27g of clay, 12g of lime slag and 12g of phosphogypsum, respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.3mm;
[0057] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 18 g of water and 7 g of an anti-vibration agent are added and stirred for 27 min to obtain a mixed mud;
[0058] S6: The mixed mud is passed through the assembly line into the aging warehouse and sealed for aging for 3 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 27°C and the pressure is 500KPa;
[0059] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0060] S8: Coat 4g of reinforcing agent on the surface of the brick, send it into a drying room and dry it at 54℃ for 4h, 64℃ for 6.5h, and 90℃ for 9h. Then send the dried brick to a tunnel kiln and sinter it at 1020℃ for 7h to obtain hollow coal gangue bricks with excellent seismic performance.
[0061] Embodiment 4: A hollow coal gangue brick with excellent earthquake resistance comprises the following steps:
[0062] S1: 9.5 g of straw was carbonized at 650°C for 2.8 h, and after cooling, 4.5 g of steel slag powder, 7 g of bamboo charcoal, 4.5 g of silicon dioxide, and 7 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0063] S2: 11 g of straw mixture was added to 4.5 g of water, stirred for 2.6 h, and then 2.5 g of water reducer was added. After mixing, the mixture was stirred at 58 °C for 33 min, and then dried in a spray drying equipment for 4.5 h to obtain an anti-seismic agent.
[0064] S3: Add 26g of rubber powder into a mixer, dry mix for 7min, then add 7g of silicon dioxide, 4.5g of calcium lignin sulfonate, 4g of sodium metasilicate, 4.5g of carboxymethyl cellulose and 9.5g of water and stir for 4.5min, finally add 2.5g of water reducer and stir for 24min to obtain a reinforcing agent;
[0065] S4: using a hammer crusher to crush 75g of coal gangue, 29g of calcium carbide mud, 54g of red mud, 28g of clay, 18g of lime slag and 14g of phosphogypsum, respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.4mm;
[0066] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 18.5 g of water and 8 g of an anti-vibration agent are added and stirred for 28 min to obtain a mixed mud;
[0067] S6: The mixed mud enters the aging warehouse through the assembly line and is sealed for aging for 3 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 28°C and the pressure is 550KPa;
[0068] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0069] S8: Coat 4.5g of reinforcing agent on the surface of the brick, send it into a drying room and dry it at 56℃ for 4.5h, 66℃ for 7h, and 95℃ for 9.5h. Then send the dried brick to a tunnel kiln and sinter it at 1030℃ for 7.5h to obtain hollow coal gangue bricks with excellent seismic performance.
[0070] Embodiment 5: A hollow coal gangue brick with excellent earthquake resistance comprises the following steps:
[0071] S1: 10 g of straw was carbonized at 700 °C for 3 h, and after cooling, 5 g of steel slag powder, 8 g of bamboo charcoal, 5 g of silicon dioxide, and 8 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0072] S2: 12g of straw mixture was added to 5g of water, stirred for 3h, then 3g of water reducer was added, mixed and stirred at 60°C for 35min, and dried in a spray drying equipment for 5h to obtain an anti-seismic agent;
[0073] S3: Add 30g of rubber powder into a mixer, dry mix for 8min, then add 8g of silicon dioxide, 5g of calcium lignin sulfonate, 5g of sodium metasilicate, 5g of carboxymethyl cellulose and 10g of water and stir for 5min, finally add 3g of water reducer and stir for 25min to obtain a reinforcing agent;
[0074] S4: using a hammer crusher to crush 80g of coal gangue, 30g of calcium carbide mud, 55g of red mud, 30g of clay, 20g of lime slag and 15g of phosphogypsum, respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.5mm;
[0075] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 20g of water and 10g of an anti-vibration agent are added and stirred for 30min to obtain a mixed mud;
[0076] S6: The mixed mud is passed through the assembly line into the aging warehouse and sealed for aging for 3 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 30°C and the pressure is 600KPa;
[0077] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0078] S8: Coat 5g of reinforcing agent on the surface of the brick, send it into a drying room and dry it at 60℃ for 5h, 70℃ for 8h, and 100℃ for 10h. Then send the dried brick to a tunnel kiln and sinter it at 1050℃ for 8h to obtain hollow coal gangue bricks with excellent seismic performance.
[0079] Comparative Example 1:
[0080] Compared with Example 1, this comparative example does not add anti-seismic agent during the preparation process of hollow coal gangue bricks with excellent anti-seismic performance. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, hollow coal gangue bricks with excellent anti-seismic performance are obtained.
[0081] Comparative Example 2:
[0082] Compared with Example 1, this comparative example does not add a reinforcing agent during the preparation of the hollow coal gangue bricks with excellent seismic performance. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, hollow coal gangue bricks with excellent seismic performance are obtained.
[0083] Comparative Example 3:
[0084] S1: 8 g of straw was carbonized at 500 °C for 2 h, and after cooling, 3 g of steel slag powder, 5 g of bamboo charcoal, 3 g of silicon dioxide, and 5 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0085] S2: 8g of straw mixture was added to 3g of water, stirred for 2h, 1g of water reducer was added, mixed and stirred at 55°C for 30min, and dried in a spray drying equipment for 3h to obtain an anti-seismic agent;
[0086] S3: Add 20g of rubber powder into a mixer, dry mix for 5min, then add 5g of silicon dioxide, 3g of calcium lignin sulfonate, 2g of sodium metasilicate, 3g of carboxymethyl cellulose and 8g of water and stir for 3min, finally add 1g of water reducer and stir for 20min to obtain a reinforcing agent;
[0087] S4: using a hammer crusher to crush 60g of coal gangue, 25g of calcium carbide mud, 50g of red mud, 20g of clay, 10g of lime slag and 10g of phosphogypsum respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.2mm;
[0088] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 17 g of water is added and stirred for 25 min to obtain a mixed mud;
[0089] S6: The mixed mud enters the aging warehouse through the assembly line and is sealed for aging for 2 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 25°C and the pressure is 400KPa;
[0090] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0091] S8: Coat 3g of reinforcing agent and 5g of anti-seismic agent on the surface of the brick, send it into a drying room and dry it at 50℃ for 3h, 60℃ for 5h, and 80℃ for 8h. Then send the dried brick to a tunnel kiln and sinter it at 1000℃ for 6h to obtain hollow coal gangue bricks with excellent anti-seismic performance.
[0092] Comparative Example 4:
[0093] S1: 8 g of straw was carbonized at 500 °C for 2 h, and after cooling, 3 g of steel slag powder, 5 g of bamboo charcoal, 3 g of silicon dioxide, and 5 g of polypropylene fiber were added, mixed, and crushed to obtain a straw mixture;
[0094] S2: 8g of straw mixture was added to 3g of water, stirred for 2h, 1g of water reducer was added, mixed and stirred at 55°C for 30min, and dried in a spray drying equipment for 3h to obtain an anti-seismic agent;
[0095] S3: Add 20g of rubber powder into a mixer, dry mix for 5min, then add 5g of silicon dioxide, 3g of calcium lignin sulfonate, 2g of sodium metasilicate, 3g of carboxymethyl cellulose and 8g of water and stir for 3min, finally add 1g of water reducer and stir for 20min to obtain a reinforcing agent;
[0096] S4: using a hammer crusher to crush 60g of coal gangue, 25g of calcium carbide mud, 50g of red mud, 20g of clay, 10g of lime slag and 10g of phosphogypsum respectively, and sieving to obtain a mixed raw material, wherein the particle size of the mixed raw material is 0.2mm;
[0097] S5: After the mixed raw materials are treated by an electromagnetic iron remover, 17g of water, 3g of a reinforcing agent and 5g of an anti-vibration agent are added and stirred for 25min to obtain a mixed mud;
[0098] S6: The mixed mud enters the aging warehouse through the assembly line and is sealed for aging for 2 days, during which time it is sprayed with moisture, and the aging temperature is maintained at 25°C and the pressure is 400KPa;
[0099] S7: The aged mixed mud is homogenized and then fed into a brick making machine to be made into brick blanks;
[0100] S8: Send the bricks into a drying room and dry them at 50°C for 3 hours, 60°C for 5 hours, and 80°C for 8 hours. Then send the dried bricks into a tunnel kiln and sinter them at 1000°C for 6 hours to obtain hollow coal gangue bricks with excellent seismic performance.
[0101] Comparative Example 5:
[0102] Compared with Example 1, this comparative example only increases the particle size of the mixed raw material from 0.2 mm to 2 mm, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, hollow coal gangue bricks with excellent seismic performance are obtained.
[0103] Comparative Example 6:
[0104] Compared with Example 1, this comparative example only increases the aging time from 2 days to 10 days, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, hollow coal gangue bricks with excellent seismic performance are obtained.
[0105] Comparative Example 7:
[0106] Compared with Example 1, the only difference in this comparative example is that the gradient drying is replaced by "drying at 50°C for 3h, drying at 60°C for 5h, and drying at 80°C for 8h" with "drying at 80°C for 3h, drying at 60°C for 5h, and drying at 50°C for 8h". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, hollow coal gangue bricks with excellent seismic performance are obtained.
[0107] Performance Testing:
[0108] Compressive strength test:
[0109] Referring to GB13544-2000 "Sintered porous bricks" testing standard, a NYL-600 pressure testing machine was used to test the compressive strength of the hollow coal gangue bricks prepared in Examples 1 to 5 and Comparative Examples 1 to 7.
[0110] Water absorption performance test:
[0111] The hollow gangue bricks prepared in Examples 1 to 5 and Comparative Examples 1 to 7 were cleaned and numbered on the surface, and then dried in an electric oven at 105-110°C to constant weight. After removing dust, the dry weight G0 was measured. After the dried sample was soaked in water for 24 hours (water temperature 20°C), the sample was taken out, the surface moisture was wiped off with a wet towel, and it was weighed quickly. The mass of water seeping out of the weighing pan during weighing should also be included in the water absorption mass. The obtained mass is the wet weight after soaking for 24 hours G 24 .
[0112] Water absorption rate after 24h immersion in water at room temperature = (G 24 -G0) / G0×100%
[0113] Thermal conductivity:
[0114] With reference to the test standard of JGJ51-2002 "Technical Specification for Lightweight Aggregate Concrete", the coal gangue hollow bricks prepared in Examples 1 to 5 and Comparative Examples 1 to 7 were tested for thermal conductivity.
[0115] Table 1 Summary of experimental data in Examples 1 to 5 and Comparative Examples 1 to 7
[0116]
[0117]
[0118] Data Analysis:
[0119] It can be seen from Table 1 that the hollow coal gangue bricks with excellent seismic performance prepared by the present invention have better seismic performance and mechanical properties;
[0120] This may be because the anti-seismic performance and mechanical properties of hollow bricks are improved by adding anti-seismic agents and reinforcing agents during the preparation of hollow bricks; the straw ash in the anti-seismic agent can enhance the compressive strength of hollow bricks and help solidify the brick body; the silica in the anti-seismic agent and reinforcing agent can increase the hardness and durability of the brick body, form a stable silicon-oxygen bond network, and improve the mechanical strength of hollow bricks. The performance of hollow bricks is enhanced by adding anti-seismic agents during the preparation of hollow bricks and by coating reinforcing agents on the surface of bricks; at the same time, the particle size, aging time and drying time of the raw materials are adjusted to achieve the best performance effect;
[0121] As no anti-seismic agent was added to Comparative Example 1 and no reinforcing agent was added to Comparative Example 2, it can be seen from Table 1 that the compressive properties and mechanical properties of the prepared hollow gangue bricks decreased. This may be because the components in the anti-seismic agent and the reinforcing agent can improve the mechanical properties of the hollow bricks, the straw ash can enhance the compressive strength of the hollow bricks and help the solidification of the brick body, and the silicon dioxide can increase the hardness and durability of the brick body, and can form a stable silicon-oxygen bond network to improve the mechanical strength of the hollow bricks.
[0122] In Comparative Example 3, since the anti-seismic agent is added to the raw materials instead of being coated on the surface of the brick, and in Comparative Example 4, since the reinforcing agent is added to the raw materials instead of being coated on the surface of the brick, it can be seen from Table 1 that the compressive resistance and mechanical properties of the prepared hollow coal gangue bricks are reduced. This may be because the rubber powder and carboxymethyl cellulose in the reinforcing agent can produce better cross-linking during the brick coating process, and carboxymethyl cellulose can enhance the viscosity of the reinforcing agent, making the coating more uniform and the performance better. When added to the raw materials, this effect is reduced; while the anti-seismic agent contains a small amount of raw materials, when coated on the surface of the brick, the raw materials may fall off easily, resulting in poor performance;
[0123] In Comparative Example 5, only the particle size of the mixed raw materials is increased from 0.2 mm to 2 mm. From Table 1, it can be seen that the compressive performance and mechanical properties of the prepared hollow gangue bricks are reduced. This may be because the particle size becomes larger, the surface area increases, and it is not easy to mix the raw materials evenly. The hollow bricks are sintered more loosely and more unevenly, which leads to the reduction of the compressive performance and mechanical properties of the hollow bricks.
[0124] Comparative Example 6 only increases the aging time from 2 days to 10 days, and Comparative Example 7 only replaces the gradient drying from "drying at 50°C for 3h, drying at 60°C for 5h, and drying at 80°C for 8h" to "drying at 80°C for 3h, drying at 60°C for 5h, and drying at 50°C for 8h". It can be seen from Table 1 that the compressive properties and mechanical properties of the prepared hollow coal gangue bricks decrease. This may be because the aging time increases and the cost increases accordingly. After the aging time is too long, the aging effect is less obvious. The high-temperature to low-temperature gradient drying may cause the center of the brick body to fail to reach a sufficient temperature, resulting in incomplete drying, affecting the mechanical strength and durability of the brick.
[0125] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0126] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A hollow coal gangue brick with excellent seismic performance, characterized in that: The invention is prepared from the following raw materials in parts by weight: 60-80 parts of coal gangue, 25-30 parts of calcium carbide mud, 50-55 parts of red mud, 20-30 parts of clay, 10-20 parts of white ash slag, 10-15 parts of phosphogypsum, 5-10 parts of anti-seismic agent, 3-5 parts of reinforcing agent, and 17-20 parts of water; The anti-seismic agent is prepared from straw, steel slag powder, bamboo charcoal, silicon dioxide, polypropylene fiber and water reducing agent; The reinforcing agent is prepared from rubber powder, silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose and a water reducing agent.
2. The hollow coal gangue brick with excellent earthquake resistance according to claim 1, characterized in that: The preparation method of the anti-seismic agent is as follows: Step A1: carbonizing the straw at 500-700° C. for 2-3 hours, adding steel slag powder, bamboo charcoal, silicon dioxide, and polypropylene fiber after cooling, mixing and crushing to obtain a straw mixture; Step A2: Add the straw mixture into water, stir for 2-3 hours, add a water reducer, mix, stir at 55-60° C. for 30-35 minutes, pass into a spray drying device and dry for 3-5 hours to obtain an anti-seismic agent.
3. The hollow coal gangue brick with excellent earthquake resistance according to claim 2, characterized in that: In step A1, the mass ratio of straw, steel slag powder, bamboo charcoal, silicon dioxide and polypropylene fiber is 8-10:3-5:5-8:3-5:5-8.
4. The hollow coal gangue brick with excellent earthquake resistance according to claim 2, characterized in that: In step A2, the mass ratio of the straw mixture, water and water reducing agent is 8-12:3-5:1-3.
5. The hollow coal gangue brick with excellent earthquake resistance according to claim 1, characterized in that: The preparation method of the enhancer is as follows: Add rubber powder into a mixer, dry mix for 5-8 minutes, then add silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose and water and stir for 3-5 minutes, finally add a water reducer and stir for 20-25 minutes to obtain a reinforcing agent.
6. The hollow coal gangue brick with excellent earthquake resistance according to claim 5, characterized in that: The mass ratio of the rubber powder, silicon dioxide, calcium lignin sulfonate, sodium metasilicate, carboxymethyl cellulose, water and water reducing agent is 20-30:5-8:3-5:2-5:3-5:8-10:1-3.
7. The hollow coal gangue brick with excellent earthquake resistance according to claim 1, characterized in that: The preparation method of the hollow coal gangue brick with excellent earthquake resistance is as follows: Step B1: using a hammer crusher to crush coal gangue, calcium carbide mud, red mud, clay, lime slag and phosphogypsum respectively, and sieving to obtain a mixed raw material; Step B2: After the mixed raw materials are treated by an electromagnetic iron remover, water and an anti-vibration agent are added and stirred for 25-30 minutes to obtain a mixed mud; Step B3: The mixed mud material is put into the aging warehouse through the assembly line and sealed for aging for 2-3 days, during which time it is sprayed with moisturizing agent; Step B4: The aged mixed mud material is homogenized and then fed into a brick making machine to be made into brick blanks; Step B5: coating a reinforcing agent on the surface of the bricks, sending the bricks into a drying chamber for gradient drying, and then sending the dried bricks into a tunnel kiln for sintering to obtain hollow coal gangue bricks with excellent earthquake resistance.
8. The hollow coal gangue brick with excellent earthquake resistance according to claim 7, characterized in that: The particle size of the mixed raw material in step B1 is 0.2-0.5 mm.
9. The hollow coal gangue brick with excellent earthquake resistance according to claim 7, characterized in that: The aging in step B3 is maintained at a temperature of 25-30° C. and a pressure of 400-600 KPa.
10. The hollow coal gangue brick with excellent earthquake resistance according to claim 7, characterized in that: The gradient drying in step B5 is drying at 50-60°C for 3-5h, drying at 60-70°C for 5-8h, and drying at 80-100°C for 8-10h; The sintering temperature in step B5 is 1000-1050° C., and the sintering time is 6-8 hours.
Citation Information
Patent Citations
Ore tailings ceramsite air brick and preparation method thereof
CN103420666A